Advances on Broadband and Wireless Computing, Communication and Applications Proceedings of the 13th International Conference on Broadband and Wireless Computing, Communication and Applications (BWCCA-2018) - Barolli, Leonard; Leu, Fang-Yie.; Enokido, Tomoya; Chen, Hsing-Chung.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2019)
This book presents on the latest research findings, and innovative research methods and development techniques related to the emerging areas of broadband and wireless computing from both theoretical and practical perspectives. Information networking is evolving rapidly with various kinds of networks with different characteristics emerging and being integrated into heterogeneous networks. As a result, a number of interconnection problems can occur at different levels of the communicating entities and communication networks' hardware and software design. These networks need to manage an increasing usage demand, provide support for a significant number of services, guarantee their QoS, and optimize the network resources. The success of all-IP networking and wireless technology has changed the way of life for people around the world, and the advances in electronic integration and wireless communications will pave the way for access to the wireless networks on the fly. This in turn means that all electronic devices will be able to exchange the information with each other in a ubiquitous way whenever necessary.
Efficient Resource Allocation for Residential Smart Buildings using Integrated Cloud and Fog Environment in Smart Grid -- Cloud Computing Based Resource Allocation by Random Load Balancing Technique -- Shortest Job First Load Balancing Algorithm for Efficient Resource Management In Cloud -- Modified Shortest Job First for Load Balancing in Cloud-Fog Computing -- Big Data Analytics for Price and Load Forecasting in Smart Grids -- A Fuzzy-based System for Actor Node Selection in WSANs Considering Load Balancing of Actors -- Evaluation of Object-based Information Flow Control in P2PPS Systems -- Flexible Resource Management for Raft Clusters -- Integration of CNN and Faster R-CNN for Tire Bubble Defects Detection -- Privacy Mining from IoT-based Smart Homes -- Cooperation for Rechargeable Heterogeneous Sensor Networks.
Keywords: Telecommunication; Computational intelligence; Communications Engineering, Networks; Computational Intelligence